Multiple Antenna Adaptation for Secondary Users Using Data Rate Assessment (International Journal of Engineering and Computer Science, 2015)
In the paper a method for multiple antenna communication with switching of users between different antenna loads is presented for cognitive radios networks, this process is an enhancement to the problem of spectrum sharing, after the detection is processed for spectrum space, the paper also discusses about the CR basics and importance of spectrum management. The performance of the proposed system is assessed by calculating the total average power of primary to secondary receiver and the overall SEP (Symbol Error Probability).